2020
DOI: 10.1016/j.mayocp.2020.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture in Patients With Irritable Bowel Syndrome: A Randomized Controlled Trial

Abstract: Objective: To evaluate the effect and safety of acupuncture for the treatment of irritable bowel syndrome (IBS) through comparisons with those of polyethylene glycol (PEG) 4000 and pinaverium bromide. Patients and Methods: This multicenter randomized controlled trial was conducted at 7 hospitals in China and enrolled participants who met the Rome III diagnostic criteria for IBS between May 3, 2015, and June 29, 2018. Participants were first stratified into constipation-predominant or diarrheapredominant IBS gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 33 publications
3
67
0
3
Order By: Relevance
“…This large study of 531 patients compared acupuncture to PEG 4000/pinaverium bromide, and found that acupuncture alleviated IBS symptoms, as assessed using the IBS severity scoring system (96), and improved patients' quality-oflife over the 6-week treatment period and the 12-week follow-up period. Importantly, the patients did not experience any adverse effects (97). Therefore, acupuncture appears to provide great benefits and might be a potential treatment for IBS in the future.…”
Section: Future Directionsmentioning
confidence: 81%
“…This large study of 531 patients compared acupuncture to PEG 4000/pinaverium bromide, and found that acupuncture alleviated IBS symptoms, as assessed using the IBS severity scoring system (96), and improved patients' quality-oflife over the 6-week treatment period and the 12-week follow-up period. Importantly, the patients did not experience any adverse effects (97). Therefore, acupuncture appears to provide great benefits and might be a potential treatment for IBS in the future.…”
Section: Future Directionsmentioning
confidence: 81%
“…Two SRs indicated that acupuncture produced a preferable therapeutic effect in improving IBS patients' quality of life compared with sham acupuncture or western medicine [35,36]. Of note, a latest published high-quality study including 531 patients found that acupuncture showed more effective results in reducing IBS symptoms and improving quality of life compared with pharmacologic therapies [19]. In addition, these effects could last up to 3 months, which is also in line with our consensus statement that relief of IBS symptoms can be maintained for 1 to 6 months after one course of acupuncture treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its common application in clinic, previous research evidences on acupuncture for IBS are still relatively scarce and in con ict. On the one hand, a previous Cochrane systematic review (SR) composed of 17 randomized clinical trials (RCTs) indicated that acupuncture exerted more bene cial effects than pharmacological interventions [18], which was validated again in the latest published study [19]. On the other hand, the sham acupuncture-controlled trials suggested that acupuncture achieved favourable e cacy but did not show therapeutic advantage over sham acupuncture [20,21].…”
Section: Introductionmentioning
confidence: 93%
“…Recently, two well-designed RCTs reported the effect of acupuncture on IBS. The multicenter RCT conducted by Pei et al , [ 38 ] which enrolled 531 cases of IBS-C and -D patients, compared the effect of acupuncture and PEG 4000/pinaverium on the IBS-SSS. The result showed that acupuncture was more effective than PEG 4000 or pinaverium bromide for the treatment of IBS, with effects lasting up to 12 weeks.…”
Section: Managementmentioning
confidence: 99%